2021
DOI: 10.3389/fpsyg.2021.610138
|View full text |Cite
|
Sign up to set email alerts
|

Financial Insecurity During the COVID-19 Pandemic: Spillover Effects on Burnout–Disengagement Relationships and Performance of Employees Who Moonlight

Abstract: The novel Coronavirus disease (COVID-19) has magnified the issue of financial insecurity. However, its effect on individual-organizational relations and, consequently, on organizational performance remains understudied. Thus, the purpose of this study was to explore the spillover effect of financial insecurity on the burnout–disengagement relationship during the pandemic. The authors investigate in particular whether the spillover effect influences the performance of moonlighting employees and also explore the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
34
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(35 citation statements)
references
References 70 publications
1
34
0
Order By: Relevance
“…This insecurity enhanced the level of distress and concern among workers about their job and financial futures (Menéndez-Espina et al, 2019). Also, the damage caused by the pandemic in several employment sectors and the rising levels of unemployment (Blustein et al, 2020;McKibbin and Fernando, 2020) put additional pressure on employers and organizations in terms of being both competitive and responsible for preserving the health and performance of their employees (Wilson et al, 2020;Rasdi et al, 2021). Overall, such changing working conditions require a better understanding of how employees respond to such changes and the consequences for employees' psychological and physical health and job performance.…”
Section: Introductionmentioning
confidence: 99%
“…This insecurity enhanced the level of distress and concern among workers about their job and financial futures (Menéndez-Espina et al, 2019). Also, the damage caused by the pandemic in several employment sectors and the rising levels of unemployment (Blustein et al, 2020;McKibbin and Fernando, 2020) put additional pressure on employers and organizations in terms of being both competitive and responsible for preserving the health and performance of their employees (Wilson et al, 2020;Rasdi et al, 2021). Overall, such changing working conditions require a better understanding of how employees respond to such changes and the consequences for employees' psychological and physical health and job performance.…”
Section: Introductionmentioning
confidence: 99%
“…According to Southwick and Southwick (2020), social bonding is a basic need for every human being, the loss of which can result in an increased risk of burnout. A study by Rasdi RM and co-authors also found that financial uncertainty negatively affected their work engagement and productivity [8].…”
Section: Risk Factorsmentioning
confidence: 93%
“…A sample item is "When you think about COVID-19 in general, how often do you feel hopeless?" [8] ils3. .…”
Section: Tools Used To Measure Burnout Associated With Covid-19mentioning
confidence: 98%
See 2 more Smart Citations